Effects of the Inquiry-based Teaching Approach on Vietnamese Students' Science Achievement Based on the 2015 PISA Data - Thuy, Tang Thi; Hung, Le Thai; Ha, Le Thi Hoang; Linh, Phan Thi (VNU Journal of Science: Education Research, 2019)
The inquiry-based teaching is known as one of the most active teaching methods. It is closely linked to inquiry-based science teaching to enhance students' scientific capacities. This study aims to analyze the relationship between inquiry-based teaching approach and scientific achievement of Vietnamese students based on the 2015 PISA database with a sample of 5,826 Vietnamese students aged 15. The results show that the more often the inquiry-based teaching method is used, the better the students’ scientific achievement is. The study also provides some recommendations based on research results to improve the quality of science teaching method and students’ scientific capacity.